2017
DOI: 10.2147/ott.s134684
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of pemetrexed on recurrent primary central nervous system lymphomas in China: a prospective study

Abstract: BackgroundPemetrexed, a new and novel agent for primary central nervous system lymphomas (PCNSLs), has shown to be efficient as a savage therapy for recurrent PCNSLs. However, more studies are needed. A prospective study was performed on 17 recurrent PCNSL patients with pemetrexed at Shandong Tumor Hospital in China to assess the efficacy and safety of pemetrexed for recurrent PCNSL patients.Materials and methodsThe medical records and imaging data on all the cases of recurrent PCNSL patients with pemetrexed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…It is able to inhibit the synthesis of purine and pyrimidine by blocking dihydrofolate reductase, thymidylate synthase and glycinamide ribonucleotide formyltransferase (25). Recently, pemetrexed has been reported to exhibit antitumor effects in various solid tumors (19,25). The present study aimed to determine whether pemetrexed was able to exert anticancer effects in ESCC and to elucidate the underlying molecular mechanism.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…It is able to inhibit the synthesis of purine and pyrimidine by blocking dihydrofolate reductase, thymidylate synthase and glycinamide ribonucleotide formyltransferase (25). Recently, pemetrexed has been reported to exhibit antitumor effects in various solid tumors (19,25). The present study aimed to determine whether pemetrexed was able to exert anticancer effects in ESCC and to elucidate the underlying molecular mechanism.…”
Section: Discussionmentioning
confidence: 94%
“…Pemetrexed is a clinically available multi-target antifolate cytotoxic agent (19). It is able to inhibit the synthesis of purine and pyrimidine by blocking dihydrofolate reductase, thymidylate synthase and glycinamide ribonucleotide formyltransferase (25). Recently, pemetrexed has been reported to exhibit antitumor effects in various solid tumors (19,25).…”
Section: Discussionmentioning
confidence: 99%
“…Survival data and toxicity profile were comparable as well. 35 A retrospective study of pemetrexed as salvage for not only relapsed PCNSL (n=17 evaluable PCNSL) but also secondary CNSL (SCNSL; n=12) illustrated an OR rate of 64.7% (all CR) and 59.3% (with 2 CR), respectively, further illustrating efficacy of this drug in the setting of relapsed CNS lymphoma. 36 Treatment of pemetrexed has also been studied in combination with rituximab in a prospective trial with 27 patients, showed an ORR of 62.9% with 22% of patients reaching a CR.…”
Section: Non-hd-mtx-based Therapiesmentioning
confidence: 99%
“…Pemetrexed, a folate antimetabolite with a broader spectrum of activity than MTX demonstrated activity in a case series of 17 patients with recurrent PCNSL and an overall radiographic response rate of 58.8% and a median OS of 7.8 months; three patients died of infection. 76 As with MTX, the main side effects include myelosuppression, gastrointestinal reactions and infections; doses up to 900 mg/m 2 are relatively well tolerated. 77 In elderly patients, pemetrexed (600 mg/m 2 ) as induction therapy appears to be feasible and well tolerated, with a median OS of 19.5 months in a case series.…”
Section: Treatmentmentioning
confidence: 99%